The Use of Scripture in the Apocryphon of John: A Diachronic Analysis of the Variant Versions - Creech, David A. (Wissenschaftliche Untersuchungen zum Neuen Testament 2. Reihe, 2017)
Cover -- Titel -- Preface -- Table of Contents -- Chapter 1: Preliminaries -- A. Introduction -- B. History of Research -- 1. Origins and Classification of 'Gnosticism' -- a. Four Perspectives on the Origins and Classification of Gnosticism -- b. The Gnostics and Scripture -- c. Assumptions and a Few Informed Decisions -- 2. The Apocryphon of John -- a. The Apocryphon of John and Scripture: The Status Quaestionis -- b. 'Diachronic' Analyses of the Apocryphon of John -- C. Brief Overview of the Argument -- 1. Aims and Thesis -- 2. Chapter Summaries -- Chapter 2: "Indeed He Said Through the Prophet" -- A. Introduction -- B. The Apocryphon and the Biblical Text: Two Common Misperceptions -- 1. Rejection of the Jewish and Christian Scriptures -- a. Karen King: Deep Engagement with Scripture but Ultimately a Rejection of It -- b. Gerard Luttikhuizen: Engagement with Scripture to Demonstrate Its Inadequacies -- c. Alastair H. D. Logan: A Dispute about Proper Interpretation -- 2. Intentional Misreading of Scripture: Reverse or 'Protest' Exegesis -- a. Intermittent Value Reversals -- b. Scriptural Chestnuts -- c. Inherent Meaning? -- d. Criticism ≠ Rejection -- e. Summary -- C. The Biblical Text as Foundational -- 1. Biblical Theology in the Apocryphon of John -- a. The Arrogant Boast -- b. Summary -- 2. The Apocryphon of John's Structural Dependence on the Biblical Text -- a. The Structure of the Apocryphon of John -- b. A Piece of Rewritten Scripture -- 3. Exegetical 'Proofs' -- a. The 'Breath of Life' -- b. Flesh of My Flesh! -- c. The Repentance of God -- 4. Summary of Findings -- D. Conclusion -- Chapter 3: "Not as Moses Said" -- A. Introduction -- B. Moses the Unreliable Witness -- 1. The Rhetoric of Citation -- 2. Framing the Rejection: The Savior Laughs -- C. Not as Moses Said… but Just as Moses Said -- 1. Lack of Substantial Disagreement.